2011
DOI: 10.1371/journal.pone.0027599
|View full text |Cite
|
Sign up to set email alerts
|

The PHD Finger of Human UHRF1 Reveals a New Subgroup of Unmethylated Histone H3 Tail Readers

Abstract: The human UHRF1 protein (ubiquitin-like containing PHD and RING finger domains 1) has emerged as a potential cancer target due to its implication in cell cycle regulation, maintenance of DNA methylation after replication and heterochromatin formation. UHRF1 functions as an adaptor protein that binds to histones and recruits histone modifying enzymes, like HDAC1 or G9a, which exert their action on chromatin. In this work, we show the binding specificity of the PHD finger of human UHRF1 (huUHRF1-PHD) towards unm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 41 publications
5
45
0
Order By: Relevance
“…16 Remarkably, the first zinc atom coordinates a loop, the so-called prePHD that precedes the canonical PHD-fold. This structural feature was first identified in the UHRF1 PHD domain and its detailed function still needs to be determined.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…16 Remarkably, the first zinc atom coordinates a loop, the so-called prePHD that precedes the canonical PHD-fold. This structural feature was first identified in the UHRF1 PHD domain and its detailed function still needs to be determined.…”
mentioning
confidence: 99%
“…This structural feature was first identified in the UHRF1 PHD domain and its detailed function still needs to be determined. 16,17 It was suggested that the prePHD might be essential for the right orientation of residue C316, which makes contact with H3K4. 16 However, if analyzed in isolation the PHD does not much discriminate the modification status of H3K4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The non-canonical (a C4C4 topology) PHD fingers of DNA (cytosine-5)-methyltransferases recognize unmodified H3, coupling histone tail association with DNA methylation, necessary for gene repression (Ooi et al 2007). A more complex interplay between the unmodified H3-binding PHD finger and the neighboring H3K9me3-binding tandem Tudor domain (TTD) of UHRF1 is required for epigenetic inheritance of DNA methylation (Arita et al 2012;Cheng et al 2013;Lallous et al 2011;Liu et al 2013;Rajakumara et al 2011;Rothbart et al 2012Rothbart et al , 2013Wang et al 2011;Xie et al 2012). Binding of the BPTF PHD finger to H3K4me3 stabilizes the nucleosomeremodeling NURF complex at chromatin, enhancing NURF-catalyzed nucleosome sliding and activation of developmental genes Wysocka et al 2006).…”
Section: Crosstalk To Dna Methylation and Chromatin Remodelingmentioning
confidence: 99%
“…The extended PHD finger of UHRF1 utilizes a distinct mechanism to bind unmodified H3 (Arita et al 2012;Cheng et al 2013;Lallous et al 2011;Liu et al 2013;Rajakumara et al 2011;Rothbart et al 2012Rothbart et al , 2013Wang et al 2011; Xie Fig. 2.3 The molecular mechanism of binding of the PHD finger to unmodified H3 tail.…”
Section: Recognition Of Unmodified H3mentioning
confidence: 99%